2(2x-1)-27=

Simple and best practice solution for 2(2x-1)-27= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2x-1)-27= equation:


Simplifying
2(2x + -1) + -27 = 0

Reorder the terms:
2(-1 + 2x) + -27 = 0
(-1 * 2 + 2x * 2) + -27 = 0
(-2 + 4x) + -27 = 0

Reorder the terms:
-2 + -27 + 4x = 0

Combine like terms: -2 + -27 = -29
-29 + 4x = 0

Solving
-29 + 4x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '29' to each side of the equation.
-29 + 29 + 4x = 0 + 29

Combine like terms: -29 + 29 = 0
0 + 4x = 0 + 29
4x = 0 + 29

Combine like terms: 0 + 29 = 29
4x = 29

Divide each side by '4'.
x = 7.25

Simplifying
x = 7.25

See similar equations:

| -2(3t-4)+4t=2t-5 | | 140=-7(1+7p) | | 3m+2(m+2)=13-(2m-5) | | 3m+2(m+2)=13-(2m-5) | | 14x+35=315 | | X*0.6666666666666667=34 | | 49+-1x=129+-9x | | -3+6x-x=42 | | 4+3x=4(4x+6) | | -4(v+4)=9v-3 | | 6x+7(x+1)=20 | | t=5.3(4)+9.5 | | -2+.66x=8 | | 49+-1x=129 | | 3x+2(3x+11)=112 | | 13.7b-3=3-4b | | 2.65=3(1+x)+x | | 3+7p-4=p+6p-1 | | 7x+8=7(x-8) | | -4+3k=12+k | | -222=6(7a-2) | | 8n-16=24+3n | | 3+7p-4+p=6p-1 | | 1y=-5x+b | | -2.3y=-4.5 | | 11(-8)=x | | 190=x+.07x | | (x^2-3)(3x^2+4x-1)= | | .33x-9=11 | | 5x-6y=-19 | | 1x-41=3 | | -2(v+2)=2v-4+2(3v+1) |

Equations solver categories